Intraventricular Hemorrhage in a Term Neonate: Manifestation of Protein S Deficiency- A Case Report - Shahriar SAHRIARIAN; Parvin AKBARI; Elahe AMINI; Hosein DALILI; Tahereh ESMAEILNIA SHRIVANY; Nikoo NIKNAFS; Mamak SHARIAT; Vafa GHORBAN SABAGH (Tehran University of Medical Sciences, 2016)
Protein S (PS) is an antithrombotic plasma protein that plays essential roles in limiting thrombus formation in the anticoagulant system. Protein S deficiency is related with recurrent thrombosis. Here, the authors report a case of a term neonate with severe PS deficiency in year 2015, Imam Hospital, Tehran, Iran, that had seizures and intraventricular hemorrhage (IVH) since the age of 3 days. Nine-month follow-up did not show any developmental problems and MRI showed no hemorrhage.